Non-Performing Loans in Jordan - Aledeimat, Shadi Ratib Mohammade (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The issue of non-performing loans has been a major area of concern in Jordan. This study was focused on analysing a quantitative study in Jordan on non-performing loans, by deriving data from 12 banks in Jordan. The data used for the analysis were extracted from 2001 to 2019. Several objectives were analysed in this study. These objectives include; investigation of bank specific determinants of non-performing loans, the analysis of macroeconomic variables of non-performing loans and an overall analysis of non-performing loans in Jordan. The data were analysed using e-views, which were later interpreted. Moreover, results from the correlation matrix indicated that CAR, LD, NL, GDP, EMP have a negative relationship with non-performing loans, and ROA, LTOA, INF, CRED, and BUDG have a positive relationship with the dependent variable. In addition, regression results shows that among bank specific variables CAR, ROA, DOA, LD and LTOA were found to be statistically significant and that increases in these banks' variables would affect the non-performing loans negatively. Beyond that, it was determined that only inflation among macroeconomic variables would affect the non-performing loans statistically significantly and positively. Keywords: Non-performing Loans, Jordan Banks, Macroeconomic Factors.

ÖZ: Bankacılık sektöründeki tahsili gecikmiş alacaklar Ürdün'de önemli bir endişe kaynağı olmuştur. Bu çalışma, Ürdün'deki 12 bankadan veri toplayarak tahsili gecikmiş alacaklar üzerine nicel bir araştırmanın analizine odaklanmıştır. Analiz için kullanılan veriler 2001-2019 yılları arasında bu bankalardan alınmıştır. Bu çalışmada bir seri analiz yapılmıştır. Bunlar arasında; takipteki kredilerin bankaya özgü belirleyicilerinin incelenmesi, takipteki kredilerin makroekonomik değişkenlerinin analizi ve Ürdün'deki takipteki kredilerin genel analizi yer almaktadır. Veriler E-Views kullanılarak tahminler yapılmış ve yorumlanmıştır. Korelasyon matrisinden elde edilen sonuçlar CAR, LD, NL, GSYİH, ÇYP'nin tahsili gecikmiş kredilerle negatif ilişki içerdiğini ve ROA, LTOA, INF, CRED ve BUDG'nin bağımlı değişkenlerle pozitif ilişki içerdiğini göstermiştir. Bunun yanında regresyon sonuçları CAR, ROA, DOA, LD ve LTOA gibi bankalara ait değişkenlerdeki artışların tahsili gecikmiş alacakları olumsuz etkiledikleri istatistiksel olarak anlamlı bulunmuştur. Bunun ötesinde makroekonomik değişkenler arasında yalnızca enflasyon tahsili gecikmiş olacakları istatiksel olarak anlamlı ve olumlu yönde etkilediği tespit edilmiştir, ekonomilerdeki istikrarsızlığın tahsili gecikmiş olacakların artmasına neden olacağı bulunmuştur. Anahtar Kelimeler: Takipteki Krediler, Ürdün Bankaları, Makroekonomik Faktörler.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2020. Supervisor: Prof. Dr. Mustafa Besim.
Keywords: Banking and Finance; Economic Conditions and Development--Jordan; Bank Loans--Non-Performing Loans; Non-performing Loans, Jordan Banks, Macroeconomic Factors